2001
DOI: 10.1053/rapm.2001.21090
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal and epidural anesthesia for labor and cesarean delivery in a patient with Guillain-Barre syndrome

Abstract: Careful evaluation and documentation of the patient's baseline neurological status, a thorough discussion with the patient regarding the risks and benefits of the technique for labor analgesia, and an appreciation of the limited experience with this kind of clinical situation are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…[58][59][60] However, case reports of regional anesthesia use in patients with GBS are generally limited to the obstetric population. [61][62][63][64] Some patients with GBS may have autonomic instability and subsequently experience an exaggerated response to neuraxial blockade, 63 whereas other patients exhibit a normal response to neuraxial anesthesia. 61,64 Although there have been reports of successful neuraxial anesthesia in parturients with GBS, the theoretical concern of local anesthetics interacting with peripheral myelin or direct nerve trauma cannot be ignored.…”
Section: Guillain-barré Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60] However, case reports of regional anesthesia use in patients with GBS are generally limited to the obstetric population. [61][62][63][64] Some patients with GBS may have autonomic instability and subsequently experience an exaggerated response to neuraxial blockade, 63 whereas other patients exhibit a normal response to neuraxial anesthesia. 61,64 Although there have been reports of successful neuraxial anesthesia in parturients with GBS, the theoretical concern of local anesthetics interacting with peripheral myelin or direct nerve trauma cannot be ignored.…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“…[61][62][63][64] Some patients with GBS may have autonomic instability and subsequently experience an exaggerated response to neuraxial blockade, 63 whereas other patients exhibit a normal response to neuraxial anesthesia. 61,64 Although there have been reports of successful neuraxial anesthesia in parturients with GBS, the theoretical concern of local anesthetics interacting with peripheral myelin or direct nerve trauma cannot be ignored. 21 There is some evidence to suggest that epidural anesthesia may precipitate or reactivate GBS hours to weeks after surgery.…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“…In addition, there is no clear evidence that epidural anesthesia causes Guillain-Barré syndrome yet. Several cases have been reported that epidural anesthesia was successfully performed during cesarean delivery of Guillain-Barré syndrome patients, in which all patients are fully recovered after the anesthesia [7,11,12]. Furthermore Hebl et al reviewed the medical chart of 139 patients with a history of CNS disorder who received neuraxial anesthesia or analgesia from 1988 to 2000, and found no case of new or worsening neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CSE can be a good option in pregnant women with a variety of serious medical conditions: CSE anesthesia or analgesia was successfully used in a parturient with severe myasthenia gravis (D'Angelo and Gerancher, 1998), idiopathic hypertrophic sub-aortic stenosis (Ho et al, 1997), mitral stenosis (Ngan Kee et al, 1999), dilated cardiomyopathy (Shnaider et al, 2001), Guillain-Barre syndrome (Vassiliev et al, 2001), Laron syndrome (Bhatia and Cockerham, 2011), tetralogy of Fallot (Arendt et al, 2011), Liddle's syndrome (Hayes et al, 2011), Wegener's granulomatosis with subglottic stenosis (Engel et al, 2011).…”
Section: Cse Anesthesia In Obstetricsmentioning
confidence: 99%